The Implementation of ESP to The Students of FEB Unismuh Makassar - Nurjannah Nurjannah; Andi Tenri Ampa; Nur Qalbi (University of Darussalam Gontor, 2023)
The aims of this Research were: (1) to find out the implementation about the content of English for Specific Purpose Materials by students of IED at FEB at UNISMUH Makassar (2) to investigate the Lecturer’s Strategy in Teaching English for Specific Purpose. This study used descriptive qualitative method. Subject of this research was lecturer of IED at FEB at UNISMUH Makassar. The procedure of this Research is that researcher gives observation and documentation to lecturer. The results of this study showed that: first, the implementation of ESP materials focused on their academic studies and used related to the absolute and variable characteristics, the second the Lecturer’s strategy used Direct Teaching Strategy and Mastery Learning Strategy of ESP has be able of IED students. English materials needed by students of Islamic Economic study program is an interesting and useful material for them in the future, especially in their future career. Students also expect interesting material that is easy to understand and based on their desires. The researcher hopes that the results of this study can help the teaching lecturers to be used to make ESP based English teaching materials as they wish.